2011
DOI: 10.1016/j.aat.2011.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Performance of ‘Intubating LMA’ and ‘Cobra PLA’ as an aid to blind endotracheal tube insertion in patients scheduled for elective surgery under general anesthesia

Abstract: We conclude that CPLA can be used as an effective conduit for blind endotracheal intubation with cuffed PVC tube and has comparable efficacy in tracheal intubation as that with ILMA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Darlong et al . [ 15 ] performed a comparison between the intubating LMA and the CobraPLA as an aid to blind endotracheal tube insertion in adult patients. They found the success with the CobraPLA to be 87% compared with 90% when using the intubating LMA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Darlong et al . [ 15 ] performed a comparison between the intubating LMA and the CobraPLA as an aid to blind endotracheal tube insertion in adult patients. They found the success with the CobraPLA to be 87% compared with 90% when using the intubating LMA.…”
Section: Discussionmentioning
confidence: 99%
“…In their study on adults, Darlong et al . [ 15 ] similarly reported a longer intubation time with the use of the CobraPLA than with the use of the intubating LMA. This difference might be due to the longer time needed to maneuver the FOB and the tracheal tube through the grills at the ventilating orifice of the CobraPLA which sometimes leads to changing of the direction of the bronchoscope tip.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effectiveness of the first attempts of intubation was 60.13%, and the overall effectiveness was 86%. The highest intubation effectiveness was obtained by Mathew et al [24] with 98%, whereas Darlong et al [21] achieved 87%.…”
Section: Discussionmentioning
confidence: 89%
“…Gaszynska et al [19] obtained 97% within an average time of 28.2 seconds. A shorter intubation time was obtained using the ILMA by Sherren et al [20] (22.8 seconds), Darlong et al [21] achieved an effectiveness of 90% during intubation using ILMA, and, in the tests performed by Garzón Sánchez et al [22], the effectiveness was 90%. However, Sastre et al [23] showed an effectiveness of 70%.…”
Section: Discussionmentioning
confidence: 93%